PALSAR-2 satellite remote sensing data for geological structure mapping: Peninsular Malaysia - Pour, Amin Beiranvand (2015)
The ALOS-2 was launched on May 24, 2014 as successor of ALOS-1. PALSAR-2 of the ALOS-2 has been significantly improved from the ALOS-1's PALSAR in all aspects including resolution, observation band, and time lag for data provision. Particularly, a HV channel (cross-polarization) is also used in the ScanSAR observation mode, thus a further increase in amount of information for geological structural mapping at regional scale in tropical environments. In this investigation, two ScanSAR mode dual polarization level 3.1 PALSAR-2 scenes were used for geological structural mapping of the entire Peninsular Malaysia. The median spatial convolution filter was used for noise removal and smoothing the PALSAR images. For identifying linear features in particular directions and edge enhancement in the spatial domain, directional convolution filters were applied to the median resultant image. Geological structural features such as transcrustal faults, ductile deformation zones (folds systems), shear zones, granite intrusions, regional foliations and brittle disjunctive structures (faults and fractures) detected in Peninsular Malaysia. The boundary between the Gondwana-derived terranes, dividing major lineaments between geological belts, subduction zone and collisional mountain range are obviously recognizable in the images. Major transcrustal lineaments such the Bentong-Raub Suture Zone (BRSZ) and Lebir Fault Zone were identified. The Main Range granites located in the west of the BRSZ appear in the image, which extends to the north of Peninsular Malaysia. Consequently, detailed analysis of structural features using PALSAR-2 remote sensing data in tropical environments is particularly useful to define the general geological structural trends, tectonic framework, deformation history and determining kinematics of the region.